The Antecedents of Consumption Value and Its Impact on Customer Behavior; a Study of Batik Cloth on Non-Javanese Indonesia Millennial - Ferdi Antonio; Putri Astika (Journal of International Conference Proceedings (JICP), 2019)
Changes in the current lifestyle has led millennial customers to have awareness about their cloth in daily life to accentuate their personality. In the other side, batik cloth industry is growing rapidly and contribute to the domestic economic. Despite the advancement of cloth printing technology, business competition in the batik industry need to balance their production with the essence of batik as an Indonesia ethnic product to preserve its soul as a valuable heritage of Indonesia culture. Having an understanding about how the customer perceive the value of batik cloth contributes to the effective marketing approach, especially for the local medium enterprises. This research was aimed to study the influence of customer diversity seeking and attitude toward the ethnic culture toward the purchase intention and willingness to share positive electronic word of mouth of the batik cloth, mediating by social value, emotional value and epistemic value as the focus of the research while moderated by ethnic embeddedness. The conceptual model was modified from the previous studies by added e-WOM as a relevance variable in digital era. The research model was implied on non-Javanese millennial customer of batik cloth to segregate the ethnicity perception. Primary data obtained by convenience sampling through the online questionnaire. The eligible sample was collected from 360 respondents who met the criteria. Data were analyzed by Structural Equation Modelling (SEM) and processed by SmartPLS 3.0. The result revealed that both customer diversity seeking and attitude toward the ethnic culture have significant effect on the consumption value. All of the three values which are social, emotional and epistemic shown significantly positive impact on e-WOM and customer purchase intention while ethnic embeddedness has proven to have the moderation effect on epistemic value and social value. Interestingly, social value was found as the strongest predictor of purchase intention. This research provides new insights in understanding consumer behavior towards batik cloth product as well as suggested practical implications that could help batik producers to implement an effective marketing strategy through the digital channel.